Indigenous women leading the defense of human rights from abuses related to mega-projects: Impacting corporate behavior — overcoming silencing practices - Tapias Torrado, Nancy (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2022)
In the face of extreme violence, some Indigenous women-led social movement organizations that defend human rights in the context of abuses committed in connection to mega-projects have achieved favorable changes in corporate practices (success). In the predominantly patriarchal, capitalist and racist context of Latin America, what explains the success (or not) of Indigenous women-led mobilizations regarding the most politically and economically powerful actors in the world? My doctoral study is dedicated to responding to this question. In this article, I offer a very brief overview of that study. Thus, I provide some details about my research model in order to then introduce the acción trenzada theoretical framework that emerges from it. In light of that framework and the case of Lenca leader Berta Cáceres in Honduras, I next discuss aspects of a dynamic of forces where criminalization as a silencing practice is used against mobilizations led by Indigenous women human rights defenders, and how they are overcoming it.